On a Heuristic Analysis of Highly Fractionated 2n Factorial Experiments - Joachim Kunert; Corinna Auer (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
The paper deals with a method for the analysis of highly fractionated factorial designs proposed by Raghavarao and Altan (2003). We show that the method will find "active" factors with almost any set of random numbers. Once that an alias set is found active, Raghavarao and Altan (2003) claim that their method can resolve the alias structure of the design and identify which of several confounded effects is active. We show that their method cannot do that. The error in Raghavarao and Altan's (2003) arguments lies in the fact that they treat a set of highly dependent (sometimes even identical) F-statistics as if they were independent.
Keywords: 519; Fractional factorial designs; half-normal plot; heuristic arguments; active effects; alias set; Faktorenanalyse; Experiment; Heuristisches Verfahren; Theorie